Beberapa Kriteria Pembebanan Optimum Ekonomi Alat-alat Pembangkitan Termis - Mak Sioe Tho (Journal of Mathematical and Fundamental Sciences, 1964)
Ichtisar. Metoda pembebanan dan perentjanaan daripada alat2 pembangkitan tenaga listrik jang bekerdja setjara parallel dan untuk optimum ekonomi telah diperkembangkan setjara memuaskan. Dalam artikel ini dibahas keriteria2 sederhana untuk merentjanakan setjara optimum ekonomi sistim-sistim jang ketjil, padamana beberapa generator bekerdja setjara parallel, dan kehilangan2 transmisi dapat diabaikan.Abstract. The method of loading and scheduling of parallel operating power plants for optimum economy has been fairly well developed. For small system where several generators are operating in  parallel and transmission losses can be neglected, simple criterions for economic scheduling and its limitation are discussed in this paper.